For a General Theory of Health: preliminary epistemological and anthropological notes - Naomar de Almeida Filho (Cadernos de Saúde Pública)
In order to conduct a preliminary evaluation of the conditions allowing for a General Theory of Health, the author explores two important structural dimensions of the scientific health field: the socio-anthropological dimension and the epistemological dimension. As a preliminary semantic framework, he adopts the following definitions in English and Portuguese for two series of meanings: disease = patologia, disorder = transtorno, illness = enfermidade, sickness = doença, and malady = moléstia. He begins by discussing some sociological theories and biomedical concepts of health-disease, which, despite their limitations, can be used as a point of departure for this undertaking, given the dialectical and multidimensional nature of the disease-illness-sickness complex (DIS). Second, he presents and evaluates some underlying socio-anthropological theories of disease, taking advantage of the opportunity to highlight the semeiologic treatment of health-disease through the theory of "signs, meanings, and health practices". Third, he analyzes several epistemological issues relating to the Health theme, seeking to justify its status as a scientific object. Finally, the author focuses the discussion on a proposal to systematize various health concepts as an initial stage for the theoretical construction of the Collective Health field.